Effect of Ferric Carboxymaltose Versus Low-Dose Intravenous Iron Therapy and Iron Sucrose on the Total Cost of Care in Patients with Iron Deficiency Anemia: A US Claims Database Analysis - Winghan Jacqueline Kwong; Kevin Wang; Peng Wang; Ralph Boccia (Adis, Springer Healthcare, 2024)
Abstract Background and Objective Iron deficiency is the most common cause of anemia. We compared the effect of ferric carboxymaltose (FCM), low-dose intravenous (IV) iron (LDI), and iron sucrose on total cost of care in patients with iron-deficiency anemia (IDA) from a US health plan perspective. Methods We conducted a retrospective claims analysis using the IQVIA PharMetrics Plus database. Patients with index (first) claims of FCM and LDI and a medical claim associated with IDA between 1 January 2017 and 31 December 2019 were included. Monthly total healthcare and inpatient and outpatient costs after receiving index IV iron for patients in the treatment cohorts were compared using a generalized linear model with gamma distribution and log-link. Results The overall study cohort included 37,655 FCM, 44,237 LDI, and 27,461 iron sucrose patients. Mean per-patient-per-month numbers of IV iron infusions for FCM, LDI, and iron sucrose were 0.20, 0.34, and 0.37, respectively. Compared with baseline, the FCM group had greater reductions in the number of hospital admissions and smaller increases in the number of outpatient visits in the 12 months post-IV iron therapy than LDI and iron sucrose, translating to significantly lower total healthcare cost (post-index adjusted cost ratio for total cost: 0.96 and 0.92, respectively; both P < 0.0001). Conclusions Higher drug acquisition cost of FCM relative to LDI and iron sucrose was offset by significantly lower inpatient and outpatient costs in the 12 months post-IV iron therapy. These results support the economic value of FCM for patients with IDA receiving IV iron therapy.